Alopesia Areata Dengan Pengobatan Triamcinolone Acetonide - Wizar Putri Mellaratna; Richy Dara Perdana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Alopecia areata (AA) is a condition characterized by sudden local hair loss without signs of skin inflammation or scarring. Data regarding the incidence of alopecia areata in Indonesia is still scanty, a retrospective study at Cipto Mangunkusumo Hospital Jakarta showed that the diagnosis of alopecia areata was the most common type of baldness in skin and genital polyclinics from 2009-2011 (39.7%). This case report was obtained from primary data through history taking, physical examination and supporting examination. The patient came with complaints of baldness on the scalp that occasionally itch. Another complaint is the growth of grey hair in areas that are bald and break easily. Experienced baldness appeared for the first time 3 months ago. On examination of the dermatological status, efflorescence of bald patches was clearly demarcated, on almost the entire scalp with the largest lesion on the right temporal and on the edge of the baldness growing white hairs that were easily broken. The location of the capitis region, the size varies (lenticular, numular, plaque), round / oval shape with regional distribution. On investigation, scalp scrapings with 10% KOH did not reveal hyphae and spores, anti-HIV and non-reactive VDRL, routine blood examinations revealed leukocytosis. Patients were treated with intralesional corticosteroids, topical corticosteroids and minoxidil according to the alopecia areata treatment algorithm.